2005
DOI: 10.1080/13693780500064771
|View full text |Cite
|
Sign up to set email alerts
|

The radiological spectrum of pulmonary aspergillosis

Abstract: Imaging findings in the pulmonary aspergilloses can answer important clinical questions. Steroid-responsive chronic asthma due to allergic bronchopulmonary aspergillosis can be differentiated from simple asthma by computed tomography (CT) evidence of extensive and severe central bronchiectasis, mucoid impaction, or small airways lesions. The simple aspergilloma can be differentiated from the complex aspergilloma by the absence of: constitutional symptoms, para-cystic lung opacities, cyst expansion, or progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 47 publications
0
46
0
6
Order By: Relevance
“…The halo sign may be found in many other situations: as a result of metastasis, bronchoalveolar carcinoma, bronchiolitis obliterans organising pneumonia, eosinophilic pneumonia or other fungal infection [78]. GREENE [79] found that 94% of 235 patients with a confirmed diagnosis of IPA had at least one nodular region. In another report on HRCT chest findings in febrile neutropenic patients with pneumonia, the findings associated with IPA were ill-defined nodules (67%), groundglass appearance (56%), and consolidation (44%) [80].…”
Section: Diagnosismentioning
confidence: 99%
“…The halo sign may be found in many other situations: as a result of metastasis, bronchoalveolar carcinoma, bronchiolitis obliterans organising pneumonia, eosinophilic pneumonia or other fungal infection [78]. GREENE [79] found that 94% of 235 patients with a confirmed diagnosis of IPA had at least one nodular region. In another report on HRCT chest findings in febrile neutropenic patients with pneumonia, the findings associated with IPA were ill-defined nodules (67%), groundglass appearance (56%), and consolidation (44%) [80].…”
Section: Diagnosismentioning
confidence: 99%
“…In contrast, the presence of centrilobular micronodules and/or tree-in-bud without any nodule with a halo sign was defined as an airway-invasive disease ( Figure 1B). 7,9,[11][12][13] As consolidations may occur with both aspergillosis-induced hemorrhagic infarctions (ie, angioinvasive disease) and Aspergillus bronchopneumonia (ie, airway-invasive disease), consolidations were not considered when differentiating between the 2 entities. 10,12,13 Fiberoptic bronchoscopy was performed within 24 hours of the baseline HRCT.…”
Section: Lung Ct Scan and Fiberoptic Bronchoscopymentioning
confidence: 99%
“…6 However, up to 40% of patients with IPA do not present with a nodule with a halo sign. 7 Some recent data have shown that other CT scan findings may be the only signs present in non-neutropenic patients with IPA, demonstrating the necessity of considering these less characteristic CT scan features for the diagnosis of IPA. 8,9 In this context, some authors have previously identified 2 different patterns of IPA, relying on correlations between histology and CT scan patterns: angioinvasive pulmonary aspergillosis is characterized by vascular invasion by Aspergillus and a nodule with a halo sign, whereas airway-invasive aspergillosis is characterized by the destruction of the bronchiolar wall by Aspergillus and centrilobular micronodules and tree-in-bud opacities.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with early lesions characterized by pulmonary nodules with halos had higher treatment response rates (52.4% versus 29.1%). 43 Moreover, a survival advantage for voriconazole recipients was observed (70.8% compared to 57.9%, a 22% improvement (χ 2 = 5.063, P = 0.024)). Despite this, response among allogeneic HSCT recipients remained suboptimal (32.4% for voriconazole versus 13.3% for CAB).…”
Section: Primary Therapymentioning
confidence: 92%